Discursive representations of secondary vocational schools students in the teachers discourse (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This study gives an account of the critical discourse analysis (ADC) carried out in an investigation, more applied to 151 technical professors, who work in the differentiated levels of secondary vocational schools with high level of vulnerability. This phase sought to establish discursive representations towards students, when teachers relate the concepts of EMTP, poverty and family. The corpus was analyzed from the three-dimensional model Fairclough. The results reproduce two social discourses, that of the state and that of the family, concealing a domination by installing a false social autonomy in the poorest student populations, projected on a determinism, when there is no chance of overcoming poverty.
Keywords: Critical discourse analysis; linguistic resources; teacher discourse; vocational/technical secondary education